Analysis of existing passenger traffic by mode of transport and assessment the competitiveness high-speed traffic in Ukraine - Shevchenko, Anna; Bugaec, Natalya; Murygina, Nadiia; Korostelov, Yevhen; Viselga, Gintas (International Conference “Environmental Engineering”, 2020)
The article analyses the volume of passenger traffic from 1990 to 2019 for land, water and air transport. From the materials obtained and the experience of the networks of European and world high-speed railways, goals are set. High-speed lines designed exclusively for passenger traffic. This moment plays an important role in reducing the cost of construction, increasing the market and economic profitability. According to the data from the State Statistics Service of Ukraine, it is possible to calculate the passenger flow based on the known parameters for 2020–2032 in the direction of Kiev-Lviv. The design of high-speed lines should meet general requirements aimed at satisfying the basic characteristics of a high-speed railway system, which works in conjunction with the European High-Speed Railway network. The compatibility of the parameters of high-speed lines with the parameters of traditional lines is part of the operational requirements for the gradual introduction of a network of high-speed railways. Possible scenarios to achieve the required compatibility should cover all subsystems.
Keywords: passengers; traffic; various modes of transport; high-speed railway system; high-speed lines; network of railways; network of highways; passenger flow analysis